THE EFFECT OF SOCIAL COMMUNITY CONTROLS ON INCREASING SEXUAL VIOLENCE AGAINST WOMEN - Ramadan, Muhammad (Universitas Negeri Semarang (UNNES), 2018)
Women are creatures of God Almighty who must be protected, even though gender equality has been done with men. Therefore women must be protected from all forms of intimidation, harassment, exploitation, violence both physically and psychologically. Because the nature of women in the eyes of the social and religious eyes have differences with men, as the nature of women is the weakest god creature. Even in law, women have different protections compared to men. This writing is in the form of descriptive narrative which means describing using available legal materials which are then processed based on the theories obtained and using normative methods based on library studies, namely by collecting various kinds of literature consisting of books, journals, and documents others relating to violence and sexual harassment and social control of these crimes. Sexual crime experienced by women in Indonesia is caused by the weak social control in the community that makes the bond of social ties not well established, causing women to be lower in the eyes of the perpetrators who commit violence against women. report the actions that occur, thus there will be omission of these conditions so as to make the perpetrators freely commit sexual violence against women. Therefore the role of community social control is very necessary to protect women.